The More-than-Human Ethics of an Underwater Hotel: Care in Alloútopian Tourism - Vannini, Phillip; Vannini, April (GeoHumanities, 2025)
Based on sensory ethnographic fieldwork carried out at three underwater hotels, and drawing in particular from our research at the Pemba Island's (Tanzania) Manta Resort's Underwater Room, in this paper we interpret underwater hotel stays as a kind of alloútopian tourism with the potential to transform relations between human guests and resident marine species-a potential afforded by the architectural design of the submerged residence. Our interviews with the architect, owner, and manager of the Underwater Room will reveal how such design is intended to attune the human guests' attention to the wonders of the local aquatic environment and resident sea life, stimulate enchantment, elicit care, and awaken response-ability.